2016
DOI: 10.1007/s10162-016-0594-4
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain Synchrony to Envelope Structure Supports Behavioral Sensitivity to Single-Formant Vowel-Like Sounds in Noise

Abstract: Vowels make a strong contribution to speech perception under natural conditions. Vowels are encoded in the auditory nerve primarily through neural synchrony to temporal fine structure and to envelope fluctuations rather than through average discharge rate. Neural synchrony is thought to contribute less to vowel coding in central auditory nuclei, consistent with more limited synchronization to fine structure and the emergence of average-rate coding of envelope fluctuations. However, this hypothesis is largely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 66 publications
4
26
0
Order By: Relevance
“…These results suggest that both rate and synchronization representation of periodicity might exist at the level of the IC. Henry et al (2017) also showed that IC neurons in awake budgerigar encoded the vowel-like sounds by the neural synchrony and variations in average discharge rate related the envelope structure. Studies of the correlation between the behaviourally measured sensitivity to amplitude-modulated signals and neural responses in the IC showed that the synchronized temporal representation was more correlated with behavioral performance than rate representation for envelope detection in awake budgerigar ( Henry et al, 2016 ).…”
Section: Discussionmentioning
confidence: 92%
“…These results suggest that both rate and synchronization representation of periodicity might exist at the level of the IC. Henry et al (2017) also showed that IC neurons in awake budgerigar encoded the vowel-like sounds by the neural synchrony and variations in average discharge rate related the envelope structure. Studies of the correlation between the behaviourally measured sensitivity to amplitude-modulated signals and neural responses in the IC showed that the synchronized temporal representation was more correlated with behavioral performance than rate representation for envelope detection in awake budgerigar ( Henry et al, 2016 ).…”
Section: Discussionmentioning
confidence: 92%
“…Degraded midbrain response synchrony in mice with profound AN loss also suggest the possibility of impaired envelope sensitivity (Chambers et al, 2016). Future behavioral experiments in the budgerigar may provide special insight into these open questions, considering previous work on complexsound perception in this species (Carney et al, 2013;Dent et al, 2000;Dooling et al, 2000;Dooling and Searcy, 1981;Henry et al, 2017bHenry et al, , 2017aHenry et al, , 2016Okanoya and Dooling, 1987) and evidence of increased central gain after KA exposure (Henry and Abrams, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Experiments were performed in four matching acoustic test chambers (Industrial Acoustics; 0.30 m 3 ) lined with sound-absorbing foam (see Henry et al, 2017bHenry et al, , 2017aHenry et al, , 2016 detailed behavioral methods). Each chamber contained an overhead loudspeaker (Polk Audio MC60), house light, and a video camera for monitoring the animal's behavior.…”
Section: Behavioral Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal response properties of the midbrain neurons convey additional information related to both the formant locations and f0. This temporal information in midbrain responses is important in explaining formant discrimination thresholds in a noise background in the parakeet, an animal model that has discrimination thresholds comparable to human listeners (Henry et al, 2017). Future studies of the representations of vowels using these computational models should include both average rate and temporal response metrics.…”
Section: Resultsmentioning
confidence: 99%